Subjective socioeconomic status moderates depression’s impact on fairness perception in the ultimatum game: A moderated mediation model - Yin Hanmo; Rozainee Khairudin; Shi Yixin; Zhang Xi; Chen Xinyu; Syakirien Yusoff; Nasrudin Subhi (PLoS ONE, 2025)
Individuals with depression often exhibit cognitive distortions in socioeconomic decision-making, particularly in interpreting fairness. However, the role of subjective socioeconomic status in shaping these distortions remains underexplored. This study investigates how depression influences fairness perception and rejection behavior in the Ultimatum Game. Specifically, it is to examine whether the fairness perception of unfair offers mediates the association between depression and the rejection rate of unfair offers, and whether subjective socioeconomic status moderates this relationship. 274 participants completed the CES-D scale to assess depressive symptoms, the MacArthur Scale to measure subjective socioeconomic status, and participated in a modified UG to evaluate fairness perception and rejection rates. Mediation and moderated mediation analyses were conducted using PROCESS Model 7. The results showed that individuals with higher levels of depression tended to perceive unfair offers as more fair, which subsequently led to fewer rejections. Crucially, this mediation effect was significant only among individuals with high subjective socioeconomic status. For low subjective socioeconomic status individuals, depression did not significantly alter the fairness perception of unfair offers. These findings suggest that subjective socioeconomic status shapes the cognitive consequences of depression, highlighting the importance of accounting for socio-cognitive contextual factors in understanding how depression affects social decision-making processes.